2016
DOI: 10.1007/s11121-016-0636-5
|View full text |Cite
|
Sign up to set email alerts
|

Technical Assistance to Enhance Prevention Capacity: a Research Synthesis of the Evidence Base

Abstract: Despite the availability of many evidence-based prevention interventions (EBIs), gaps exist in bringing these programs into widespread practice. Technical assistance (TA) is a strategy for enhancing the readiness of practitioners to implement EBIs. Although many millions of dollars are spent on TA each year, there is little consensus about what the essential features of TA are and how to provide TA with quality. A broad-based research synthesis methodology was used for analyzing the current evidence base for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 31 publications
6
110
1
Order By: Relevance
“…A review of evidence about technical assistance to enhance prevention capacity suggested that specific tasks and content varied widely across studies [25]. As described earlier, centralized technical assistance in this context has been a multicomponent strategy consisting of educational sessions, facilitation and the development of action plans.…”
Section: Discussionmentioning
confidence: 99%
“…A review of evidence about technical assistance to enhance prevention capacity suggested that specific tasks and content varied widely across studies [25]. As described earlier, centralized technical assistance in this context has been a multicomponent strategy consisting of educational sessions, facilitation and the development of action plans.…”
Section: Discussionmentioning
confidence: 99%
“…We were, however, unable to locate any reviews or syntheses of TA models or frameworks but did locate a number of reviews of related practices (Bertram, Suter, Bruns, & O'Rourke, 2011;Chapman & Moore, 2010;Hodge & Turner, 2016;Leeman et al, 2017;Paulsell, Del Grosso, & Supplee, 2014;Wandersman, Chien, & Katz, 2012). Two reviews in particular proved particularly informative in terms of the present scoping review (Katz & Wandersman, 2016;Meyers, Durlak, & Wandersman, 2012). Meyers et al (2012) reviewed the literature with a focus on identifying the critical steps or actions for fostering high quality implementation of a "specific set of [TA] activities to put into practice an activity or program of known dimensions" (Fixsen, Naoom, Blase, Friedman, & Wallace, 2005, p. 5).…”
Section: Technical Assistance Core Elementsmentioning
confidence: 88%
“…To address these two challenges, partners engaging in program scale‐up typically employ a combination of external implementation support, usually originating from the Support system, to translate both implementation and program science into local resources and abilities within the Community system (Chinman et al, 2016; Katz & Wandersman, 2016; Rushovich, Bartley, Steward, & Bright, 2015; Spoth & Greenberg, 2011). In addition to the Support system, implementation partners work with local implementation teams, teams of system or organizationally‐bound leaders and managers who have a combination of program knowledge, implementation science knowledge, data‐driven improvement expertise, and system change experience to drive the pace of day‐to‐day implementation and scaling activities within the local community environment (Aldridge et al, 2016a; Brown et al, 2014; Fixsen et al, 2013; Higgins, Weiner, & Young, 2012; Metz & Bartley, 2012).…”
Section: Community Capacity Coach: An Innovative Strategy To Address mentioning
confidence: 99%